Tacitus and the Tacitean Tradition. - Luce, Torrey James; Woodman, Anthony John. (Princeton : Princeton University Press, 2014)
In this volume distinguished scholars from both sides of the Atlantic explore the work of Tacitus in its historical and literary context and also show how his text was interpreted in the sixteenth through eighteenth centuries. Discussed here, for example, are the ways predilections of a particular age color one's reading of a complex author and why a reexamination of these influences is necessary to understand both the author and those who have interpreted him. All of the essays were first prepared for a colloquium on Tacitus held at Princeton University in March 1990. The resulting volume.
Frontmatter -- CONTENTS -- INTRODUCTION -- RONALD SYME-A Brief Tribute / Bowersock, G.W. -- ABBREVIATIONS -- 1. Tacitus and the Province of Asia / Bowersock, G.W. -- 2. Reading and Response in the Dialogus / Luce, T.J. -- 3. Speech and Narrative in Histories / Keitel, Elizabeth -- 4. Tacitus and Germanicus / Pelling, Christopher -- 5. In maiores certamina·. Past and Present in the Annals / Ginsburg, Judith -- 6. Amateur Dramatics at the Court of Nero: Annals 15.48-74 / Woodman, A.J. -- 7. Tacitean Prudentia and the Doctrines of Justus Lipsius / Morford, Mark -- 8. Tacitus Noster: The Germania in the Renaissance and Reformation 152 / Kelley, Donald R. -- 9. Politics, Taste, and National Identity: Some Uses of Tacitism in Eighteenth-Century Britain / Weinbrot, Howard D. -- BIBLIOGRAPHY -- LIST OF CONTRIBUTORS -- GENERAL INDEX -- INDEX OF PASSAGES
Print version record.
eBooks on EBSCOhost
Keywords: Tacitus, Cornelius -- Congresses; Tacitus, Cornelius -- Congresses; Tacitus, Cornelius; Rome -- Historiography -- Congresses; HISTORY -- Essays; HISTORY -- Ancient -- Rome; Historiography; Rome (Empire); Conference papers and proceedings